Agreement between arterial and central venous values for pH, bicarbonate, base excess, and lactate. Issue 8 (20th July 2006) - Middleton, P; Kelly, A-M; Brown, J; Robertson, M
Abstract : Objective: This study aimed to determine the extent of agreement between central venous and arterial values for pH, bicarbonate, base excess, and lactate in a group of intensive care unit (ICU) patients. Methods: A prospective study of a convenience sample of patients deemed by their treating doctor to require blood gas analysis as part of their clinical care in ICU. It compared pH, bicarbonate, base excess and lactate on arterial and central venous samples taken within five minutes of each other. Data were analysed using bias (Bland–Altman) methods. Results: A total of 168 matched sample pairs from 110 patients were entered into the study. All variables showed close agreement. The mean difference between arterial and venous values of pH was 0.03 pH units, for bicarbonate 0.52 mmol/l, for lactate 0.08 mmol/l, and for base excess 0.19 mmol/l. All showed acceptably narrow 95% limits of agreement. Conclusion: Central venous pH, bicarbonate, base excess, and lactate values showed a high level of agreement with the respective arterial values, with narrow 95% limits of agreement. These results suggest that venous values may be an acceptable substitute for arterial measurement in this clinical setting.